Hydrogen Peroxide Inhibits Hepatitis C Virus Replication by Downregulating Hepatitis C Virus Core Levels through E6-Associated Protein-Mediated Proteasomal Degradation - Yoon, Hyunyoung; Jang, Kyung Lib (Cells (Basel, Switzerland), 2023)
Hepatitis C virus (HCV) is constantly exposed to considerable oxidative stress, characterized by elevated levels of reactive oxygen species, including hydrogen peroxide (H2O2), during acute and chronic infection in the hepatocytes of patients. However, the effect of oxidative stress on HCV replication is largely unknown. In the present study, we demonstrated that H2O2 downregulated HCV Core levels to inhibit HCV replication. For this purpose, H2O2 upregulated p53 levels, resulting in the downregulation of both the protein and enzyme activity levels of DNA methyltransferase 1 (DNMT1), DNMT3a, and DNMT3b, and activated the expression of E6-associated protein (E6AP) through promoter hypomethylation in the presence of HCV Core. E6AP, an E3 ligase, induced the ubiquitin-dependent proteasomal degradation of HCV Core in a p53-dependent manner. The inhibitory effect of H2O2 on HCV replication was almost completely nullified either by treatment with a representative antioxidant, N-acetyl-L-cysteine, or by knockdown of p53 or E6AP using a specific short hairpin RNA, confirming the roles of p53 and E6AP in the inhibition of HCV replication by H2O2. This study provides insights into the mechanisms that regulate HCV replication under conditions of oxidative stress in patients.